Retail productivity - Rachel Griffith; Heike Harmgart (Institute for Fiscal Studies (IFS), 2005)
Recent attention has focused on the UK's productivity gap in the retail sector. Figure 1 shows an estimate of labour productivity in retail across countries, using output per hour worked. The UK lies well behind the US, France and Germany. Reynolds at al (2005) contribute to this debate by providing a discussion of the literature, along side interviews with several UK and US retail firms. The conclusions of their paper are that, while there are many measurement issues, most of the evidence points to the fact that, on average, productivity in this sector in the UK is low and has grown slowly over recent years when compared to the US. They rightly point out that a more thorough understanding of what drives productivity in the retail sector requires a better understanding of the 'complex mix of urban characteristics, consumer preferences and competitive rivalries'. In this article we discuss some of the main issues involved in the measurement of productivity in retail, how these problems can be tackled, and we consider the interpretation of these statistics. We then discuss new work using microdata on the UK supermarket industry and conclude with a short discussion of where future research needs to look to answer the important policy questions around why the UK's productivity performance remains low in this important sector.
Keywords: 330; Arbeitsproduktivität; Einzelhandel; Vergleich; Großbritannien; Frankreich; Deutschland